2007
DOI: 10.1152/ajpregu.00128.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced alterations of phospholipid fatty acyl composition in brown adipose tissue mitochondria are independent of uncoupling protein-1

Abstract: Ocloo A, Shabalina IG, Nedergaard J, Brand MD. Cold-induced alterations of phospholipid fatty acyl composition in brown adipose tissue mitochondria are independent of uncoupling protein-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 63 publications
4
19
0
Order By: Relevance
“…7C). The elevation in the content of both 18:2 and 20:4-6 in brown fat in response to cold exposure has been repeatedly shown in mitochondria of brown fat (33)(34)(35), and we show here that the level of only one of these (20:4-6) was mitigated by group housing.…”
Section: Methodssupporting
confidence: 81%
“…7C). The elevation in the content of both 18:2 and 20:4-6 in brown fat in response to cold exposure has been repeatedly shown in mitochondria of brown fat (33)(34)(35), and we show here that the level of only one of these (20:4-6) was mitigated by group housing.…”
Section: Methodssupporting
confidence: 81%
“…Other studies have shown that, for example, surface area (Crichton et al 2009) and phospholipid content (Ocloo et al 2007) do not differ significantly between the wildtype and Ucp1KO models. This suggests that, while factors other than UCP1 content may influence basal proton conductance to some extent, they are unlikely to account for the large changes observed.…”
Section: Discussionmentioning
confidence: 78%
“…However, these alterations are not secondary to UCP1-mediated uncoupling or to any other UCP1-dependent activity. 60 The angiogenic processes in brown adipose tissue It is presently discussed whether the increased vascularization in adipose tissues is secondary to hypoxia occurring in the tissues. However, in both interscapular brown adipose tissue and in inguinal white adipose tissue, cold-acclimationinduced angiogenesis is independent of the hypoxia that can occur in tissues during stimulation 61 (but the hypoxia itself is dependent on the presence of UCP1 61 ).…”
Section: Fevers Of Different Kindsmentioning
confidence: 99%